The Role of Sleep and Sleep Deprivation in Epileptic Seizures - Kania, Joanna; Miazga, Dominika; Gęborys, Anna; Mazurek, Katarzyna; Niekurzak, Karolina; Jędrak, Maciej; Grodzińska, Weronika; Matuszewska, Julia; Dubaj, Magdalena; Fussek, Łukasz (Quality in Sport, 2026)
Background. Sleep is a fundamental physiological process that regulates brain network stability and neuronal excitability.In epilepsy sleep–wake regulation is closely linked to the occurrence of epileptiform discharges and seizure susceptibility.Sleep disturbances,deprivation,and irregular sleep–wake rhythms are recognized as modifiable factors affecting seizures,disease course,and diagnostic yield. Aim of the study. The aim of this study was to summarize the current evidence on the relationship between sleep physiology,sleep deprivation,and epileptiform brain activity,focusing on mechanisms linking sleep stages with seizure generation and the clinical relevance of sleep EEG. Material and methods. A narrative review of the literature was conducted using PubMed,Google Scholar,and selected academic sources.The analysis included original research articles,clinical studies,systematic reviews,and expert consensus papers published from 2010 through 2025. Results. The reviewed evidence shows that non–rapid eye movement (NREM) sleep, especially slow-wave sleep, promotes neuronal synchronization and interictal discharges, while rapid eye movement (REM) sleep suppresses epileptic activity. Sleep deprivation lowers seizure threshold by disrupting excitatory–inhibitory balance and sleep–wake transitions. EEG during sleep or after deprivation increases detection of epileptiform abnormalities. Irregular or fragmented sleep also increases seizure risk, even without reduced total sleep time. Conclusion. Sleep significantly influences epileptiform activity through stage-dependent mechanisms.Sleep deprivation and irregular sleep patterns are important seizure provoking factor,while sleep EEG is a valuable diagnostic tool. Recognizing sleep as a modifiable factor is important for epilepsy diagnosis and disease management.